Effect of Growth Parameters and Annealing Atmosphere on the Properties of Cu2ZnSnS4 Thin Films Deposited by Cosputtering - Arun Khalkar; Kwang-Soo Lim; Seong-Man Yu; Shashikant P. Patole; Ji-Beom Yoo (International Journal of Photoenergy)
Cu2ZnSnS4 (CZTS) thin films were deposited using the cosputtering technique. The growth parameters, such as working pressure, target powers, and postannealing atmosphere, were optimized for CZTS films deposition. A comparative study between post annealing using sulfur vapor in a quartz tube furnace and sulfurization chamber using H2S gas was carried out to optimize the kesterite Cu2ZnSnS4 phase. 10 min annealing at 530°C in the furnace in sulfur vapor eliminated all the secondary phases and formed kesterite Cu2ZnSnS4. The diffusion of sulfur in the film during the annealing process enhanced the crystallinity of the film. The kesterite Cu2ZnSnS4 phase was confirmed by X-ray diffraction, Raman scattering, and optical measurements. The film showed phonon peaks corresponding to the kesterite CZTS, high-absorption coefficient (1.1 × 105 cm−1), and desired optical direct band gap (1.5 eV).